APLIKASI BAYESIAN PROBABILITY PADA AKUISISI PENGETAHUAN PENYAKIT KEJIWAAN SKIZOFRENIA - Martalisa, Martalisa (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
In the world of mental health, information about the One of the solution to overcome this problem is to create an application information about mental illness Based on the existing knowledge base, the computer program will imitate an expert's reasoning with existing expertise in a particular knowledge base in order to solve a particular problem by providing solutions such as the workings of the experts. The method to be used is Bayesian Probability. Bayesian Probability is also very suitable for use in analyzing the acquired sufficient information and Bayesian Probability which is a method of interpretation of the probability calculus that defines the concept of conditional probability as the degree of confidence of someone who believes that the proposition is true. Testing result get 91.25% for accuracy. Key words Bayesian Probability, Expert System, Forward Chaining